A Lasting Performance: Jane Austen - Jukić-Gregurić, Tatjana (Array, 1999)
The text focuses on an exploration of the ways in which body, politics, and history - catogories rather subdued and kept at bay in Jane Austen's fiction - are represented in contemporary film and television adaptations of her novels, when the iconic and the visual are used as a means to inscribe the missing link between an old, elusive discourse and its painfully, almost frustratingly new consumers. Also, it shows how this new iconicity feeds from the powerful place of authority within the institution of literature and reinforces it in return.